Application of three-dimensional Superb micro-vascular imaging (3D-SMI) combined with quantitative blood flow analysis in the noninvasive diagnosis of renal tumors - Mao, Yiran; Yu, Chunyang; Wang, Tianqi; Li, Fangxuan; Hou, Wenjing; Wei, Xi; Mu, Jie (The Ultrasound Journal, 2025)
Objective: To investigate the diagnostic value of three-dimensional superb micro-vascular imaging (3D-SMI) combined with quantitative analysis of Area and VI in differentiating benign and malignant renal tumors.Methods: A total of 256 renal lesions from 254 patients who underwent gray-scale ultrasound (Gray US), twodimensional superb micro-vascular imaging (2D-SMI), and 3D-SMI examinations at Tianjin Medical University Cancer Institute and Hospital between January 2022 and June 2024 were retrospectively analyzed. The imaging features on Gray US, 2D-SMI and 3D-SMI were recorded. Based on 3D-SMI, Vascular Architecture were classified into five types:Type I (avascular), Type II (spotty flow), Type III (sparse flow), Type IV (encircling), and Type V (rich flow). The plane with the most abundant blood flow was selected, and the Area and VI were calculated using Image Pro Plus (IPP) software. Histopathology from surgery or biopsy served as the reference standard. The differences in Vascular Architecture, Area, and VI between benign and malignant renal tumors were compared, and their diagnostic performance was evaluated.Results: Among the 256 lesions, 70 were benign and 186 were malignant. The interobserver agreement for Vascular Architecture classification was good (Kappa = 0.803), and the consistency for Area and VI was high (ICC = 0.835 and 0.864, respectively). Benign tumors Vascular Architecture were mainly type II or III, with mean Area and VI values of 945.87 ± 568.26 (range: 68–3125) and 5.93 ± 4.95 (range: 0.23–24.73), respectively. Malignant tumors were predominantly type IV or V, with mean Area and VI values of 3694.53 ± 2612.38 (range: 93–9965) and 18.21 ± 10.83 (range: 0.69–48.13), respectively. Significant differences were observed in Vascular Architecture, Area, and VI between benign and malignant lesions (all P < 0.001). The area under the ROC curve (AUC) values for 3D-SMI Vascular Architecture, Area, VI, 2D-SMI, and Gray US were 0.813, 0.807, 0.859, 0.750, and 0.718, respectively. VI demonstrated the highest diagnostic performance, with a cutoff value of 8.19 (sensitivity: 82.26%; specificity: 85.51%). Among benign subtypes, there were no significant differences in Vascular Architecture or Area (P > 0.05), while the VI of oncocytoma was significantly higher than epithelioid angiomyolipoma (EMAL), metanephric adenomas (MA), and angiomyolipoma (AML)(P < 0.01). Among malignant subtypes, clear cell renal cell carcinoma (ccRCC) showed distinct Vascular Architecture compared with papillary renal cell carcinoma(pRCC), chromophobe renal cell carcinoma(chRCC), and Xp11.2 translocation/TFE3 fusion-associated renal cell carcinoma(tRCC) (P < 0.01). The Area and VI of ccRCC were significantly higher than those of pRCC and chRCC (P < 0.05), but not significantly different from tRCC (P > 0.05).Conclusion: 3D-SMI provides three-dimensional visualization of Vascular Architecture. Quantitative analysis of the most vascularized plane using Area and VI differentiation between benign and malignant renal tumors, with VI demonstrating the best diagnostic efficacy. This technique offers a non-invasive diagnostic approach for renal tumors.